Optimizing Sexuality Education in Early Childhood Based on "Puppet Show" - Lestari, Sri Puji; Iswanti, Dwi Indah; haji, Son (Health Notions, 2017)
The low level of community and cultural knowledge that assumes the taboo of sexuality education in children at an early age is one of the originators of sexual abuse in children. Sexuality education that is aligned with the capacity and thinking patterns of children will help a child to protect himself from the perpetrators of abuse. The puppet show method, which uses puppets as a tool, offers a more appealing method for children. This study aims to test the effectiveness of puppet show as a method to improve early childhood knowledge about sexuality, using a pre-post test with control group design. The subjects of this study were 34 children in PAUD Tiara Hati, Tembalang District, Semarang selected by purposive sampling technique. Data were collected using questionnaire, Puppet Show module and storyteller, then analyzed using T-Test. The results show that Puppet Show can improve early childhood knowledge about sexuality.